InFUSing antisense oligonucleotides for treating ALS. Issue 4 (April 2022) - Codron, Philippe; Cassereau, Julien; Vourc'h, Patrick
Abstract : The question of a loss or toxic gain of function in FUS-related amyotrophic lateral sclerosis is still debated. Recently, Korobeynikov et al . argued that FUS mutations lead to a gain of function and showed that lowering wild-type and mutant FUS levels could be a promising therapeutic strategy.